Implementasi Data Mining Menggunakan Algoritma Hash Based Terhadap Pola Pengeluaran Obat Pada Rumah Sakit Pertamina Tarakan - Febriyan, Febriyan; Juliansyah, Rizky; Sinawati, Sinawati; Anto, Anto (Journal of Big Data Analytic and Artificial Intelligence, 2024)
The role of information systems has expanded to other layers of life, especially in the health sector. Improving service and performance productivity in the health sector, including pharmacies. This study identifies drug dispensing patterns at the Pertamina Tarakan Hospital.This research was carried out in several stages. First, create tabular transaction data. Second, determine minimum support. Third, determine the memory address. Fourth, calculate the minimum confidence. Fifth, calculate confidence, and last, make a decision.This study focuses on Rs Pertamina Tarakan to identify common spending patterns. For example, in the previous 12 months, what drug combination was most commonly administered to patients. Knowing dispensing patterns allows Rs Pertamina Tarakan to arrange the layout of medicines, resulting in more optimal and excellent service in the medicine administration department. The results showed that in 2022, three pairs of drug combinations placed close together, namely Ranitidin, Urdahex Cap first pair, Urdahex Cap, Folamil genio kap, Propylathiorasil second pair, and Propylathiorasil, Ranitidin, and Urdahex Cap  third pair.